Population pharmacokinetic and exposure‐response analysis of eptinezumab in the treatment of episodic and chronic migraine - Brian Baker; Barbara Schaeffler; Martin Beliveau; Igor Rubets; Susan Pederson; MyMy Trinh; Jeff Smith; John Latham (Wiley, 2020)
Abstract Eptinezumab is a humanized mAb that targets calcitonin gene‐related peptide and is under regulatory review for the prevention of episodic and chronic migraine (EM, CM). It is important to determine whether exposures achieved with intravenous (IV) administration of eptinezumab achieve desired pharmacologic effects. Population pharmacokinetics, including dose‐ and exposure‐response analyses, were performed using patient‐level data from the eptinezumab clinical trial program with IV doses ranging from 10 to 1000 mg in pharmacokinetic analyses or 10 to 300 mg in phase 2/3 clinical studies in patients with EM or CM. Exposure‐response analysis explored the relationship between eptinezumab exposure metrics and efficacy parameters including monthly migraine days. The pharmacokinetic profile of eptinezumab was characterized by rapid attainment of maximum plasma concentration (ie, end of IV administration) and a terminal half‐life of 27 days. Covariate analysis found that patient characteristics had no clinically significant effects on pharmacokinetic parameters and were insufficient to influence dosing. Dose‐ and exposure‐response analyses found exposure with single doses ≥100 mg was associated with greater efficacy compared with doses ≤30 mg and a plateau of effect between 100 and 300 mg. A saturable inhibitory Emax model found the exposure over 12 weeks produced by single‐dose eptinezumab 100 and 300 mg exceeded the exposure estimates required to achieve 90% of the maximal efficacy (EC90). This pharmacokinetic analysis of eptinezumab supports dosing every 12 weeks with no adjustment for patient characteristics, including exposures associated with 100‐ or 300‐mg doses producing optimal efficacy effects. The similar efficacy profiles support 100 mg as the lowest effective dose of eptinezumab.